E-Bayesian estimation for the proportional hazard rate model based on record values - KIZILASLAN, FATİH (TAYLOR & FRANCIS INC, 2019)
In this article, a new parameter estimation method, named E-Bayesian method, is considered to obtain the estimates of the unknown parameter and reliability function based on record values. The maximum likelihood, Bayesian, E-Bayesian, and hierarchical Bayesian estimates of the unknown parameter and reliability function are obtained when the underlying distribution belongs to the proportional hazard rate model. The Bayesian estimates are obtained based on squared error and linear-exponential loss functions. The previously obtained some relations for the E-Bayesian estimates are improved. The relationship between E-Bayesian and hierarchical Bayesian estimations are obtained under the same loss functions. The comparison of the derived estimates are carried out by using Monte Carlo simulations. Real data are analyzed for an illustration of the findings.
Keywords: Burr Type XII distribution; E-Bayesian estimation; Hierarchical Bayesian estimation; Proportional hazard rate model; Record values; GENERAL-CLASS; DISTRIBUTIONS